Effect of Coating on Seed Quality of Quality Protein Maize Hybrid and Storability under Hill Conditions - JYOTI SHARMA; KC DHIMAN; JK SHARMA; RK KAPILA; RAMESH KUMAR (Seed Research, 2026)
A laboratory experiment was conducted at Seed Technology Laboratory, CSK Himachal Pradesh Krishi Vishvavidyalaya, Palampur during 2014-15 to study the effect of seed coating on seed quality in HQPM 1 hybrid maize. The seeds were coated with polymer, fungicides, insecticide, polymer-fungicides and polymer-insecticide combinations and stored under ambient conditions in HDPE (high density polyethylene) inter woven bags for 12 months. Seed deteriorated and the vigour declined with increased fungal infection and insect infestation after twelve months of seed storage, irrespective of seed coating treatments. Seed coated with polymer @ 3 ml per kg of seed and vitavax 200 @ 2 g per kg of seed recorded the highest germination percentage (90.30%), seedling length (30.83 cm), field emergence (79.00%), seedling dry weight (0.696 g) and seedling vigour index (2785) up to 12 months over the untreated control and lowest seed infection (4.99%) at the end of 12 months of storage. Seed coated with Imidacloprid @ 6 ml per kg of seed had lowest insect infestation (0.50%) and seed coated with polymer @3 ml per kg of seed and vitavax 200@2 g per kg of seed.